Outbreak of white piedra in a flock of Extremeña blue hens - García Alfredo; Barraso Carmen (Veterinarski Glasnik)
This paper describes for the first time a case of avian ringworm, caused by Cutaneotrichosporon jirovecii in a small flock of Extremeña blue hens and highlights that the disease could occur in outbreak proportions, with 46.70% of cocks affected. Infected birds had white crusts on the comb, and most affected animals showed white or light brown nodules that were loosely attached to the tip of feathers, but no systemic disease signs were observed. The diagnosis of Trichosporon jirovecii was made by morphological identification, and it was confirmed by sequencing amplification product of the PCR using universal primers of the internal transcribed spacer region.